The Mediating Role of Emotional and Psychological Well-Being in the Relationship Between Digital Addiction and Academic Procrastination among Secondary School Students - Kara, Fatih (2026)
This study examined whether emotional and psychological well-being are a mediating factor in the association between digital addiction and academic procrastination among middle school students. A correlational predictive model was used with a sample of 346 students enrolled in middle schools in the province of Diyarbakır (Turkey) during the 2024–2025 academic year. Data were collected using the Digital Addiction Scale, the Academic Procrastination Scale, and the Stirling Children’s Emotional and Psychological Well-Being Scale. During the data analysis phase, examinations for extreme values, univariate and multivariate normality test, and homogeneity analyses were first performed. Subsequently, the Pearson product–moment correlation coefficient was calculated using the SPSS-23 software package to assess associations among the variables, and mediation analysis was conducted using the Hayes PROCESS Macro for SPSS. According to the results, digital addiction is a strong predictor of both academic procrastination and emotional and psychological health. Furthermore, middle school student emotional and psychological health was discovered to mediate the relationship between internet addiction and academic procrastination. The study findings were used to provide recommendations to policymakers and researchers for future quantitative and experimental studies on digital addiction and academic procrastination. Participating agencies included the Turkish Statistical Institute, Ministry of National Education, Higher Education Council, Ministry of Health, and the Information Technologies Authority.